Ultra-Wide Band Printed Microstrip Patch Antenna with Two Band Rejection Feature Asmaa H. Majeed College of Information Engineering, Al-Nahrain University, Baghdad, Iraq Correspondence - Majeed, Asmaa H. (Iraqi Journal for Electrical and Electronic Engineering, 2024)
This work presents a new design idea for a UWB printed micro strip patch antenna with two band-rejection features. The patch has an elliptical shape and its feeding using micro strip feeding line. To achieve the UWB, an elliptical slot was etched on a ground plane. The rejection of two-band is achieved with the addition of two different slots on the radiating patch, the first slot is inverted U shaped slot and the other is U-shaped slot, so there is no need for antenna’s additional size. The radiation pattern of the suggested antenna has an omnidirectional shape for the frequency band from 3.168 GHz to over 15 GHz. There is a two rejection bands, the first one covering 4.87−5.79 GHz with a center frequency of 5.42 GHz, and the other covering 7.2−8.45 GHz with a center frequency of 7.8 GHz. The chosen substrate for the current work is FR-4 having permittivity of 4.3 and thickness of 1.43 mm and the suggested antenna has a small size of 24.5×24.5mm2. The Experimental results of the manufactured antenna showed agreement with those results of the simulated one.